Legal Analysis of Receiving Funds from Money Politics in Indonesian Elections and Measures to Overcome It from the Perspective of Imam al-Ghazālī - Sa'id Chammadullah; Sohibul Hikam; Izdihar Muhammade Nahidl (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2025)
The practice of money politics has consistently been a prominent and highly debated topic in Indonesia's political landscape. The rampant occurrence of vote buying during every election cycle makes this issue crucial to examine, particularly from a legal perspective and with a focus on potential solutions. This study investigates Imam al-Ghazali's views on the legal permissibility of accepting funds derived from money politics and explores his proposed solutions to this issue. This research aims to delve into the legal framework surrounding money politics in general elections, identify effective strategies to combat it, and instill a comprehensive understanding of the ruling on accepting funds from such practices. This library research employs a qualitative descriptive approach. The primary reference for this study is Imam al-Ghazali's seminal work, Ihya’ Ulum ad-Din, supplemented by various other relevant texts by other prominent Islamic scholars. The findings indicate that the practice of money politics carries severe negative consequences and is categorized as bribery (risywah), which is expressly prohibited by the Islamic law. Consequently, according to Imam al-Ghazali, accepting funds from vote-buying is haram (forbidden), and recipients are obligated to return these assets to their rightful owners or the state treasury. The enforcement of a strict prohibition on accepting such funds is imperative, alongside concerted efforts to improve the economic conditions of society as preventive measures against this widespread issue. This study offers an in-depth understanding of the legal implications of accepting money politics funds from al-Ghazali's perspective. It also opens avenues for further discussion on money politics and its potential solutions through the lens of other Islamic scholars.